Genetic Drivers of Multidrug Resistance in Candida glabrata - Healey, Kelley R.; Jimenez Ortigosa, Cristina; Shor, Erika; Perlin, David S. (Frontiers in Microbiology, 2016)
Both the incidence of invasive fungal infections and rates of multidrug resistance associated with fungal pathogen Candida glabrata have increased in recent years. In this perspective, we will discuss the mechanisms underlying the capacity of C. glabrata to rapidly develop resistance to multiple drug classes, including triazoles and echinocandins. We will focus on the extensive genetic diversity among clinical isolates of C. glabrata, which likely enables this yeast to survive multiple stressors, such as immune pressure and antifungal exposure. In particular, over half of C. glabrata clinical strains collected from U.S. and non-U.S. sites have mutations in the DNA mismatch repair gene MSH2, leading to a partial mutator phenotype and increased frequencies of drug-resistant mutants in vitro. Furthermore, recent studies and data presented here document extensive chromosomal rearrangements among C. glabrata strains, resulting in a large number of distinct karyotypes within a single species. By analyzing clonal, serial isolates derived from individual patients treated with antifungal drugs, we were able to document chromosomal changes occurring in C. glabrata in vivo during the course of antifungal treatment. Interestingly, we also show that both MSH2 genotypes and chromosomal patterns cluster consistently into specific strain types, indicating that C. glabrata has a complex population structure where genomic variants arise, perhaps during the process of adaptation to environmental changes, and persist over time.